Takhrijul Hadis Keutamaan Ilmu Agama Melalui Hadis Bukhari Nomor 82 - Salamuddin, Ahmad; Huda , Ali Anhar Syi’bul; Sumarna , Elan; Nurhuda, Abid; Lathif , Nur Muhammad (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This research seeks to analyze the virtue of religious knowledge as well as the quality of the hadith with the focus of the research being Bukhari's hadith number 82. The approach used in the research is qualitative with the use of the method used is literature study and takhrij hadith. Data collection is done with the help of the maktabah syamilah application, jawamiul kalimi, Bukhari hadith number 82, books, journals, proceedings, reports, and papers as primary data. While documentation and valid and credible sources from the internet as secondary data. The results obtained from this study conclude that Bukhari's Hadith number 82 can be taken as proof to be practiced in everyday life because based on testing the quality of the hadith by takhrij it is categorized as a sahih hadith. When traced, the tradition was narrated by the first narrator and the last sanad, namely from Abdullah bin Umar Al Adawy who was a friend who was then narrated to the Lais bin Said Al-Fahmy line and then to two lines including Imam Bukhari and Imam Ahmad as the mudawwin of the tradition. In addition, Bukhari's Hadith number 82 is also full of lessons (wisdom) that can be taken as a lesson where the Prophet highly values religious knowledge as a pillar of life, a compass, and a guide to the path of human life and encourages his people to also study, explore, and develop world knowledge to provide for him in the future.